Availability of Nitrite and Nitrate as Electron Acceptors Modulates Anaerobic Toluene-Degrading Communities in Aquifer Sediments - Zhu, Baoli; Friedrich, Sebastian; Wang, Zhe; Táncsics, András; Lueders, Tillmann (Frontiers in Microbiology, 2020)
Microorganisms are essential in environmental pollutants degradation. Aromatic hydrocarbons, e.g., BTEX, are common aquifer contaminants, whose in situ degradation is often limited by the availability of electron acceptors. It is clear that different electron acceptors such as nitrate, iron or sulfate support the activity of distinct degraders. However, this has not been demonstrated for the availability of nitrate vs. nitrite, both of which can be respired in reductive nitrogen cycling. Here via DNA-stable isotope probing, we report that nitrate and nitrite provided in different concentrations as the electron acceptors not only modulated the microbial communities responsible for toluene degradation, but also influenced how nitrate reduction proceeded. Zoogloeaceae members, mainly Azoarcus spp., were the key toluene degraders with nitrate-only, or both nitrate and nitrite as electron acceptors. In addition, a shift within Azoarcus degrader populations was observed on the ASV level depending on electron acceptor ratios. In contrast, members of the Sphingomonadales were likely the most active toluene degraders when only nitrite was provided. Nitrate reduction did not proceed beyond nitrite in the nitrate-only treatment, while it continued when nitrite was initially also present in the microcosms. Likely, this was attributed to the fact that different microbial communities were stimulated and active in different microcosms. Together, the findings implicated that nitrate usage efficiency in bioremediation can be possibly enhanced by modulating the initial active degrader communities.